Multicentric randomized evaluation of a tricuspid valve percutaneous repair system (clip for the tricuspid valve) in the treatment of severe secondary tricuspid regurgitation Tri.Fr Design paper. (6th December 2021) - Donal, Erwan; Leurent, Guillaume; Ganivet, Anne; Lurz, Philip; Coisne, Augustin; De Groote, Pascal; Lafitte, Stephane; Leroux, Lionel; Karam, Nicole; Biere, Loic; Rouleau, Frederic; Sportouch, Catherine; et al.
Abstract: Aims: Tricuspid regurgitation (TR) is associated with significant morbidity and mortality. Its independent prognostic role has been repeatedly demonstrated. However, this valvular heart condition is largely undertreated because of the increased risk of surgical repair. Recently, transcatheter techniques for the treatment of TR have emerged, but their implications for the clinical endpoints are still unknown. Methods and results: The Tri.fr trial will be a multicentre, controlled, randomized (1:1 ratio), superior, open-label, and parallel-group study conducted in 300 patients with severe secondary TR that is considered non-surgical by heart teams. Inclusion will be possible only after core laboratory review of transthoracic and transoesophageal echocardiography and after validation by the clinical eligibility committee. A description of the mechanisms of the TR will be conducted by the core laboratory. Atrial or ventricular impacts on the severity of the secondary TR will be taken into account for the randomization. The patients will be followed for 12-month, and the primary outcome will be the Packer composite clinical endpoint [combining New York Heart Association class, patient global assessment (PGA), and major cardiovascular events]. It will test the hypothesis that a tricuspid valve percutaneous repair strategy using a clip dedicated to the tricuspid valve is superior to best guideline-directed medical therapy in symptomatic patients with severe secondary TR. Conclusion: Tri.fr will be the first randomized, academic, multicentre study testing the value of percutaneous correction in patients with severe secondary TR. Graphical Abstract: